Semiotics, Computation, Mechanical Philosophy and Freedom: A Semiotic Argument for the Existence of God? - Génova, Gonzalo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
A long tradition, which starts with the metaphor of the wax tablet presented in the Theaetetus of Plato, leads us to think that the relationship between mental representation and the represented reality is in a certain way mechanical or automatic. But the truth is that the conventional aspects of signification make it impossible to understand it as a physical- mechanical process. The computer sciences, contrary to a superficial vision, do not support but rather disprove this mechanistic conception of rationality, confirming that semiosis can only occur in free subjects, that is to say, not completely subject to the laws of matter.